“IMPACT OF STRESS MANAGEMENT AMONG THE EMPLOYEES OF BANKS” - Raju, Dr.K.Venkata Krishna; Geetha, S. (IJRDO - Journal of Applied Management Science, 2017)
The productivity of the work force is the most decisive factor as far as the success of anorganization is concerned. The productivity in turn is dependent on the psychosocial well beingof the employees. The banking organization, have been facing greater challenges in terms oftechnological revolution, service diversification and global banking. Stress is unavoidable on thepart of the employees as the systems, procedures; techniques are getting complicated with theuse of advance technology. Every employee cannot cope with such rapid changes taking place inthe jobs. This will lead to arising of stress among employees. Stress can affect one‘s health, workperformance, social life and the relationship with family members. The stressors and itsconsequences are to be understood at individual and organizational level. An attempt has beenmade through this research paper to know the reasons of stress among the bank employees andthe ways used by employees to cope with the stress generated at workplace The aim of this paperis to provide insight that will help the reader further improve his/her management competenciesin managing stress in the workplace.Stress is a fact in our daily life. When a person needs help, it means the person feelsphysically and emotionally disabled. Most people believe that their capacity and capabilities areso little to encounter high level of stress. Today, with progress in all respects, human is facingnew challenges in many different fields as if progress in turn creates new problems. Over acentury, the nature of working has been changed widely, and still these changes are in progress.Following these changes, number of illnesses has been increased, morality and human aspectsare faded and new problems are occurred every day, so that we are facing job stress which called“illness of the century”